Transcriptome Analysis Identifies Strategies Targeting Immune Response-Related Pathways to Control Enterotoxigenic Escherichia coli Infection in Porcine Intestinal Epithelial Cells - Wu, Qiong; Cui, Defeng; Chao, Xinyu; Chen, Peng; Liu, Jiaxuan; Wang, Yiding; Su, Tongjian; Li, Meng; Xu, Ruyu; Zhu, Yaohong; Zhang, Yonghong (Frontiers in Veterinary Science, 2021)
Enterotoxigenic Escherichia coli (ETEC) is an important cause of postweaning diarrhea (PWD) worldwide, resulting in huge economic losses to the swine industry worldwide. In this study, to understand the pathogenesis, the transcriptomic analysis was performed to explore the biological processes in porcine intestinal epithelial J2 cells infected with an emerging ETEC strain isolated from weaned pigs with diarrhea. Under the criteria of |fold change (FC)| ≥ 2 and P < 0.05 with false discovery rate (FDR) < 0.05, a total of 131 referenced and 19 novel differentially expressed genes (DEGs) were identified after ETEC infection, including 96 upregulated DEGs and 54 downregulated DEGs. The Gene Ontology (GO) analysis of DEGs showed that ETEC evoked biological processes specifically involved in response to lipopolysaccharide (LPS) and negative regulation of intracellular signal transduction. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that immune response-related pathways were mainly enriched in J2 cells after ETEC infection, in which, TNF, IL-17, and MAPK signaling pathways possessed the highest rich factor, followed by NOD-like receptor (NLR), C-type lectin receptor (CLR), cytokine-cytokine receptor interaction, and toll-like receptor (TLR), and nuclear factor kappa-B (NF-κB) signaling pathways. Furthermore, 30 of 131 referenced DEGs, especially the nuclear transcription factor AP-1 and NF-κB, participate in the immune response to infection through an integral signal cascade and can be target molecules for prevention and control of enteric ETEC infection by probiotic Lactobacillus reuteri. Our data provide a comprehensive insight into the immune response of porcine intestinal epithelial cells to ETEC infection and advance the identification of targets for prevention and control of ETEC-related PWD.